Occurrence and Characterization of Methicillin Resistant Staphylococcus aureus in Processed Raw Foods and Ready-to-Eat Foods in an Urban Setting of a Developing Country - Islam, Mohammad Aminul; Parveen, Sahana; Rahman, Mahdia; Huq, Mohsina; Nabi, Ashikun; Khan, Zahed Uddin Mahmood; Ahmed, Niyaz; Wagenaar, Jaap A. (Frontiers in Microbiology, 2019)
Infections by methicillin-resistant Staphylococcus aureus (MRSA) are gradually increasing in the community. In this study, we investigated a total of 162 food samples including 112 ready-to-eat (RTE) foods and 40 processed raw meat and fish samples collected from retail vendors in Dhaka, Bangladesh and determined the occurrence of toxigenic S. aureus and MRSA. Around 22% of samples were positive for S. aureus, RTE foods being more positive (23%) than the processed raw meat/fish samples (18%). Among 35 S. aureus isolates, 74% were resistant to erythromycin, 49% to ciprofloxacin and around 30% to oxacillin and cefoxitin. Around 37% of isolates were resistant to ≥3 classes of antibiotics and 26% of isolates (n=9) were identified as MRSA. Majority of the isolates were positive for enterotoxin genes (74%), followed by pvl gene (71%), toxic shock syndrome toxin (tsst) gene (17%) and exfoliative toxin genes (11%). Multi locus sequence typing (MLST) of 9 MRSA isolates identified four different types such as ST80 (n=3), ST6 (n=2), ST239 (n=2) and ST361 (n=2). spa typing of MRSA isolates revealed seven different types including t1198 (n=2), t315 (n=2), t037 (n=1), t275 (n=1), t304 (n=1), t8731 (n=1) and t10546 (n=1). To our knowledge, this is the first report entailing baseline data on the occurrence of MRSA in RTE foods in Dhaka highlighting a potential public health risk to street food consumers.